2012
DOI: 10.1309/ajcpop7apgdt9jiu
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Neoplasms Secondary to Plasma Cell Myeloma: An Intrinsic Predisposition or Therapy-Related Phenomenon?

Abstract: We describe 41 cases of myeloid neoplasms (MNs) secondary to plasma cell myeloma (PCM). The types of MN included myelodysplastic syndrome (MDS) in 34 (82.9%), acute myeloid leukemia (AML) in 4 (9.8%), and myeloproliferative neoplasm (MPN) or MDS/MPN in 3 (7.3%) cases. The latency from treatment to diagnosis of MN ranged from 9 to 384 months, with a median of 60 months. Of 37 cases with cytogenetic studies, complex abnormalities were detected in 22 (59.5%), -5(q)/-7(q) in 4 (10.8%), other abnormalities in 8 (21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…On the other hand, the occurrence of AML in this case maybe closely related to chemotherapy or radiotherapy, and so it is referred to as therapy-related AML (t-AML). At this time, it is unclear whether this represents an intrinsic predisposition or therapy-related phenomenon ( 75 ). Similarly, the pathologic procedure and pathogenesis for this case are unclear and must be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the occurrence of AML in this case maybe closely related to chemotherapy or radiotherapy, and so it is referred to as therapy-related AML (t-AML). At this time, it is unclear whether this represents an intrinsic predisposition or therapy-related phenomenon ( 75 ). Similarly, the pathologic procedure and pathogenesis for this case are unclear and must be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to treatment efficacy, the tendency to trigger secondary neoplasm development is another key factor to consider during development of novel anti-MM drugs. Early small cohort studies showed that DNA alkylating drugs might possess a higher tendency to induce secondary neoplasms [ 130 , 131 , 132 ]. However, more recent study using a 403-patient cohort suggested that the therapeutic mechanism exhibited an insignificant impact; instead, complex karyotypes are largely correlated to the risk of developing secondary neoplasms [ 133 ].…”
Section: Future Direction: Biomarker-guided Targeted Therapymentioning
confidence: 99%
“…However, more recent study using a 403-patient cohort suggested that the therapeutic mechanism exhibited an insignificant impact; instead, complex karyotypes are largely correlated to the risk of developing secondary neoplasms [ 133 ]. Nevertheless, the skewed tendency of developing myelodysplastic syndrome (MDS) [ 130 ] warrants deeper investigation into therapy-related secondary neoplasms.…”
Section: Future Direction: Biomarker-guided Targeted Therapymentioning
confidence: 99%
“…As chemotherapy for the treatment of plasma cell myeloma (PCM) includes alkylating agents, the incidence of therapy-related myeloid neoplasms such as acute myeloid leukemia, myelodysplastic syndrome (MDS), and myeloproliferative neoplasm due to prior PCM chemotherapy has increased. Several studies reported the mutagenic effect of some PCM treatment regimens on the development of MDS [ 1 2 3 ]. By contrast, cases with simultaneous presentation of PCM and MDS unrelated to prior chemotherapy are far less frequently observed than cases with MDS related to prior chemotherapy [ 4 5 6 ].…”
Section: To the Editormentioning
confidence: 99%